Hubungan Tingkat Kepatuhan Terhadap Luaran Klinis Pada Pasien Hipertensi Di Puskesmas Teladan Kota Medan - Nurhalilah Hutagalung; Kiki Rawitri; Rafita Yuniarti; Syilvi Rinda Sari (LPPM Universitas Abdurrab, 2025)
Hypertension is a non-communicable disease that remains a major health problem worldwide, especially in Indonesia, as it can cause severe complications such as stroke, kidney failure, and heart disease. The success of hypertension control does not only depend on medication but also on patients’ adherence to taking the medicine regularly. Patients with a good level of adherence are usually able to maintain stable blood pressure, thereby preventing complications. This study aims to analyze the relationship between medication adherence and clinical outcomes among hypertensive patients at Puskesmas Teladan, Medan City. This research used a non-experimental method with a cross-sectional study design involving 135 hypertensive patients who met the inclusion criteria at Puskesmas Teladan Medan during May–June 2025. Adherence data were obtained using the MMAS-8 questionnaire, while clinical outcome data in the form of patients’ blood pressure were collected through direct examination. Data were analyzed using the Spearman Rho test with the SPSS program. The results showed an average adherence score of 6.64±1.437, with systolic and diastolic blood pressure averages of 135.11±16.385 and 72.31±11.303, respectively. There was a significant relationship between medication adherence and clinical outcomes (p=0.000; r=0.463) and between adherence and blood pressure control (p=0.000; r=0.387), indicating a moderate correlation (r=0.40–0.69). It can be concluded that higher medication adherence leads to better blood pressure control and improved clinical outcomes in hypertensive patients.